Analysis of different innovative formulations of curcumin for improved relative oral bioavailability in human subjects - Purpura, Martin; Lowery, Ryan P.; Wilson, Jacob M.; Mannan, Haider; Münch, Gerald; Razmovski-Naumovski, Valentina (European journal of nutrition, 2018)
Purpose The optimal health benefits of curcumin are limited by its low solubility in water and corresponding poor intestinal absorption. Cyclodextrins (CD) can form inclusion complexes on a molecular basis with lipophilic compounds, thereby improving aqueous solubility, dispersibility, and absorption. In this study, we investigated the bioavailability of a new γ-cyclodextrin curcumin formulation (CW8). This formulation was compared to a standardized unformulated curcumin extract (StdC) and two commercially available formulations with purported increased bioavailability: a curcumin phytosome formulation (CSL) and a formulation of curcumin with essential oils of turmeric extracted from the rhizome (CEO). Methods Twelve healthy human volunteers participated in a double-blinded, cross-over study. The plasma concentrations of the individual curcuminoids that are present in turmeric (namely curcumin, demethoxycurcumin, and bisdemethoxycurcumin) were determined at baseline and at various intervals after oral administration over a 12-h period. Results CW8 showed the highest plasma concentrations of curcumin, demethoxycurcumin, and total curcuminoids, whereas CSL administration resulted in the highest levels of bisdemethoxycurcumin. CW8 (39-fold) showed significantly increased relative bioavailability of total curcuminoids (AUC 0−12 ) in comparison with the unformulated StdC. Conclusion The data presented suggest that γ-cyclodextrin curcumin formulation (CW8) significantly improves the absorption of curcuminoids in healthy humans.